Republic of Armenia : Sixth Review under the Stand-by Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2022)
Real GDP growth rebounded strongly in 2021 and early 2022, driven by a pickup in construction, trade, and services activities, and benefiting from strong policies and a gradual improvement of the pandemic, notwithstanding its various waves. In 2022, the budget aimed at continuing a gradual fiscal consolidation, while still providing temporary and targeted support to the economy, and monetary policy aimed at continuing its tightening cycle that started in late-2020 to cool down inflation. The favorable near-term outlook, however, is set to be interrupted by the spillovers from the war in Ukraine and the sanctions against Russia, given Armenia's economic links and exposure to the Russian economy. Growth has been revised down markedly this year, while inflationary pressures are expected to persist, keeping inflation above the Central Bank of Armenia's (CBA) target in 2022.